2017
DOI: 10.1038/srep41919
|View full text |Cite
|
Sign up to set email alerts
|

Visual cortex and cerebellum hyperactivation during negative emotion picture stimuli in migraine patients

Abstract: Migraines are a common and undertreated disease and often have psychiatric comorbidities; however, the abnormal mechanism of emotional processing in migraine patients has not been well clarified. This study sought to investigate the different brain functional activation to neutral, positive and negative emotional stimuli between migraine and healthy subjects. Twenty-six adults with migraines and 26 healthy adults, group-matched for sex and age, participated in this experiment. Although there were no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…4 ). The subregions of the brain with disrupted connectivity in patients were involved in the discrimination of sensory features of pain (sensory-motor cortex, posterior insula and posterior parietal cortex), cognitive processing (orbitofrontal cortex and parahippocampal gyrus), pain modulation processing (thalamus, insula, anterior cingulate cortex, and prefrontal cortex), sensory integration processing (temporal lobe) and visual information processing (occipital lobe) 26 , 31 , 48 , 49 , 51 , 55 , 60 64 . The parahippocampal gyrus exhibited disrupted connectivity with the fusiform gyrus, the temporal lobe, the occipital lobe and the parietal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). The subregions of the brain with disrupted connectivity in patients were involved in the discrimination of sensory features of pain (sensory-motor cortex, posterior insula and posterior parietal cortex), cognitive processing (orbitofrontal cortex and parahippocampal gyrus), pain modulation processing (thalamus, insula, anterior cingulate cortex, and prefrontal cortex), sensory integration processing (temporal lobe) and visual information processing (occipital lobe) 26 , 31 , 48 , 49 , 51 , 55 , 60 64 . The parahippocampal gyrus exhibited disrupted connectivity with the fusiform gyrus, the temporal lobe, the occipital lobe and the parietal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging evidence over the past decade has shown specific brain function in migraine patients is abnormal compared to normal controls [10,12,[18][19][20][21][22]. Some studies have shown "overactivity" of the visual cortex during migraine episodes [23] and interictal interval [24].…”
Section: Introductionmentioning
confidence: 99%
“…We found activation in the visual cortex and anterior cerebellum lobe/culmen during presentation of negative emotion picture stimuli in migraineurs [23]. Furthermore, migraineurs without aura exhibited dysfunction in the default mode network and sensorimotor network during the task-free state [8, 24].…”
Section: Introductionmentioning
confidence: 99%